Estrategias de marketing y su incidencia en las ventas de la Empresa Michelina Fashion store del cantón Vinces. Provincia de Los Ríos, periodo 2023. - Ronquillo Quinto, Carlos Raúl (2025)
This research focuses on evaluating the impact of marketing strategies on the sales of Michelina Fashion Store, a company dedicated to the trade of clothing in the Vinces canton, Los Ríos province, during the year 2023. The general objective of the study is to analyze how the marketing strategies implemented influence the purchasing decisions of customers and, therefore, the store's sales. An applied, field and descriptive research methodology was used in order to obtain relevant data on consumer behavior and the effectiveness of the store's marketing strategies. The surveys carried out on the store's customers provided valuable information on the perception that consumers have about various aspects of the business, such as presence on social networks, loyalty, prices, promotions, product quality, and the possibility of making online purchases. In conclusion, the research shows that while in-store marketing strategies have a positive impact on sales and customer loyalty, there are significant opportunities to strengthen the digital presence, expand promotions, and facilitate online shopping options to meet consumer preferences and further improve Michelina Fashion Store's business results.